2020
DOI: 10.1051/0004-6361/201936538
|View full text |Cite
|
Sign up to set email alerts
|

First detection of the carbon chain molecules13CCC and C13CC towards SgrB2(M)

Abstract: Context. Carbon molecules and their 13 C-isotopologues can be used to determine the 12 C/ 13 C abundance ratios in stellar and interstellar objects. C 3 is a pure carbon chain molecule found in star forming regions and in stellar shells of carbon-rich late-type stars. Latest laboratory data of 13 C-isotopologues of C 3 allow a selective search for the mono-substituted species 13 CCC and C 13 CC based on accurate ro-vibrational frequencies.Aims. Our aim was to provide the first detection of the 13 C-isotopologu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Small carbon chains, such as C 2 , C 3 , and C 5 , have been observed in several regions of the interstellar medium (ISM) (Souza & Lutz 1977;Giesen, T. F. et al 2020;Maier et al 2001;Hinkle et al 1988;Bernath et al 1989). They are expected to be the building blocks of more complex organic molecules that could explain the origin of life.…”
Section: Introductionmentioning
confidence: 99%
“…Small carbon chains, such as C 2 , C 3 , and C 5 , have been observed in several regions of the interstellar medium (ISM) (Souza & Lutz 1977;Giesen, T. F. et al 2020;Maier et al 2001;Hinkle et al 1988;Bernath et al 1989). They are expected to be the building blocks of more complex organic molecules that could explain the origin of life.…”
Section: Introductionmentioning
confidence: 99%
“…A gas and grain warm-up model proposed by Mookerjea et al has explained the abundance of C 3 in the warm envelopes of hot cores in a consistent manner [16]. Very recently, the detection of 13 C 12 C 12 C and 12 C 13 C 12 C along the line of sight towards Sgr B2(M) allowed to determine the 12 C/ 13 C element ratio in the C 3 molecules to be 20.5 AE 4.2 [17]. This value is in agreement with the elemental ratio of 20, typically observed in Sgr B2(M).…”
Section: Astrophysical Implicationmentioning
confidence: 84%
“…Spectroscopic constants were obtained and the C-C bond length was derived experimentally for each isotopologue. Furthermore, the precise line positions led to the detection of 13 C 12 C 12 C and 12 C 13 C 12 C towards Sgr B2(M) [17]. Besides all these experimental studies, important contributions came from precise theoretical work.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Giesen et al (2020) have reported the first detection of the 13 C-isotopologues of C 3 , 13 CCC and C 13 CC, towards the massive starforming region SgrB2(M), near the Galactic Center. They derived an average 12 C/ 13 C abundance ratio of 20.5±4.2, in agreement with the local value of 20 as derived from the Galactocentric trend by Milam et al (2005) for CN, CO and H 2 CO, taking into account the three molecules:…”
Section: The Importance Of C 3 Isotopic-exchange Reactionmentioning
confidence: 99%